2022
DOI: 10.7717/peerj.12701
|View full text |Cite
|
Sign up to set email alerts
|

Maple and hickory leaf litter fungal communities reflect pre-senescent leaf communities

Abstract: Fungal communities are known to contribute to the functioning of living plant microbiomes as well as to the decay of dead plant material and affect vital ecosystem services, such as pathogen resistance and nutrient cycling. Yet, factors that drive structure and function of phyllosphere mycobiomes and their fate in leaf litter are often ignored. We sought to determine the factors contributing to the composition of communities in temperate forest substrates, with culture-independent amplicon sequencing of fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…It suggests that phyllosphere microorganisms were the dominant groups in early decomposition, but as the decomposition progressed, soil bacteria entered the litter layer through raindrop splashing, wind action, and the carrying of fungal mycelium [31]. In this study, Proteobacteria, Actinobacteriota, and Acidobacteriota were the dominant nitrogen-fixing microorganisms in July and October, which is consistent with the results of soil bacterial communities in long-term time series [24], and exhibit environmental filtration [32]. Actinobacteria is a nutrient-poor bacterial community, which prefers nutrient-poor environments and has a higher concentration in extreme habitats [33].…”
Section: Differences In Bacterial Community Structure and Diversity I...supporting
confidence: 86%
“…It suggests that phyllosphere microorganisms were the dominant groups in early decomposition, but as the decomposition progressed, soil bacteria entered the litter layer through raindrop splashing, wind action, and the carrying of fungal mycelium [31]. In this study, Proteobacteria, Actinobacteriota, and Acidobacteriota were the dominant nitrogen-fixing microorganisms in July and October, which is consistent with the results of soil bacterial communities in long-term time series [24], and exhibit environmental filtration [32]. Actinobacteria is a nutrient-poor bacterial community, which prefers nutrient-poor environments and has a higher concentration in extreme habitats [33].…”
Section: Differences In Bacterial Community Structure and Diversity I...supporting
confidence: 86%
“…It has been historically challenging to translate measurements of microbial phylogenetic diversity into predictions of functional diversity (Rodriguez et al ., 2009; Djemiel et al ., 2022) because phenotypic differences are difficult to predict from genetic sequence variation alone, especially among closely related individuals (Arnold & Lutzoni, 2007; Grünig et al ., 2008; Johnson et al ., 2012; Hazard et al ., 2017; U’Ren et al ., 2019; Harrison & Griffin, 2020; Liber et al ., 2022). To address this major gap, we compared the multivariate metabolic phenotypes of sister lineages of fungal endophytes and found that lineages harbor significant and selectable phenotypic variation related to growth on plant-derived metabolites and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from each isolate was extracted by placing a small amount of fungal tissue in an alkaline-Tris solution and incubating at 95°C for 10 min to lyse the cells ( 41 ). The supernatant was used for PCR amplification with the primers ITS1f and LR3 ( 42 , 43 ).…”
Section: Methodsmentioning
confidence: 99%